Modernizing Healthcare Claims Processing: A Technical Case Study of QNXT Migration - Achyuth Reddy Lakhireddy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The implementation of the QNXT platform at Hill Physicians marks a transformative advancement in healthcare claims processing infrastructure, demonstrating the successful migration from legacy systems to modern distributed architecture. This comprehensive system overhaul encompasses multiple layers of technical innovation, including containerized microservices, sophisticated data processing capabilities, and robust integration frameworks. The migration strategy employed a careful balance of technological advancement and risk mitigation, ensuring continuous business operations throughout the transition. The article’s architecture was designed with a focus on scalability, reliability, and performance optimization, incorporating advanced features such as distributed database systems, real-time processing capabilities, and automated validation mechanisms. This article represents a significant milestone in healthcare technology modernization, showcasing the successful integration of complex healthcare data processing requirements with modern cloud-native architectural principles, while maintaining strict compliance with industry standards and operational requirements.